Neo-romantic landscapes : an aesthetic approach to the films of Powell and Pressburger - Hockenhull, Stella (Cambridge Scholars Pub., 2008)
Neo-Romantic Landscapes offers a reappraisal of the 1940s films of Powell and Pressburger focusing on their use of landscape. Questioning the established notion that the two film-makers, owing to their non-British personal roots, are located as un-British.